Niger : 2019 Article IV Consultation, Fourth Review Under the Extended Credit Facility, and Requests for Waiver of Nonobservance of a Performance Criterion, Modification of Performance Criteria, and Extension and Rephasing of the Extended Credit Facility Arrangement-Press Release; Staff Report and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2019)
Niger faces daunting development challenges, aggravated by terrorist incursions, low uranium export prices, and climate change. Nonetheless, GDP growth picked up to 6.5 percent last year- and should average above 7 percent over the next five years thanks to reforms, substantial donor support, several large-scale projects, and a one-time boost from the projected commencement of crude oil exports in 2022.